Improving the training on creating a distance learning platform in higher education: evaluating their results - Rakhmetov, Maxot; Kuanbayeva, Bayan; Saltanova, Galiya; Zhusupkalieva, Galiya; Abdykerimova, Elmira (Frontiers in Education, 2024)
The COVID-19 pandemic has had a profound impact on the world, and one of the many changes it has brought about is the shift to distance learning in Kazakhstan’s universities. However, both teachers and students were ill-prepared for this sudden change. In some remote villages, lack of internet access meant that students had no access to online classes at all. To address this issue, universities had to rent foreign platforms, but these platforms had inadequate information security measures in place. To address these challenges, it is necessary to create a robust and secure independent platform for distance learning. This platform will be particularly important for training teachers of “Informatics” in the context of distance learning. This article presents methods and schemes for creating a distance learning platform specifically for training computer science teachers. The introduction of the “Education-Online Platform” discipline at the university has yielded promising results. As a result, a distance learning platform has been created, and this new discipline has been introduced and tested in the educational program of a particular university in the training of future specialists.